The weight of a Mass : a tale of faith - Nobisso, Josephine; Szegedi, Katalin, 1963- (Westhampton Beach, N.Y. : Gingerbread House, 2002)
On the day of a royal wedding in a kingdom where everyone has grown careless in the practice of their Catholic faith, a poor widow helps reveal the true value of the Mass.
Keywords: Mass -- Fiction; Catholics -- Fiction; Faith -- Fiction; Christian life -- Fiction; Kings, queens, rulers, etc. -- Fiction